Structure and Agency in Networked, Distributed Work: The Role of Work Engagement. (April 2015) - Halgin, Daniel S.; Gopalakrishnan, Gopakumar M.; Borgatti, Stephen P.
In this article, we examine the social structure of workplace relationships (both actual and desired ties) in networked distributed work. We focus on the role of human agency in forming networks needed to succeed in this environment. In particular, we address how employee work engagement enables individuals to occupy the network positions that they need in order to succeed in networked and virtual settings. We analyze a distributed team within a large multinational firm involved in software development and delivery activities and find that highly engaged employees have personal networks that are anchored locally (i.e., strong ties with colleagues who are collocated and more transitive triples) and connect globally (i.e., strong ties with distant colleagues and more liaison brokerage ties across geographic locations). We also find a general tendency for all respondents to desire new ties that reach across global locations to improve performance at work. However, only the highly engaged employees achieve these ties highlighting the role of motivation and agency associated with engagement.